Hubungan Gaya Hidup Dengan Kejadian Stroke Di Rumah Sakit - Wijianto, Wijianto; Yuda, Wanda Kurnia (Jurnal Fisioterapi dan Rehabilitasi, 2022)
Stroke is a neurological disorder associated with vascular injury of the central nervous system. This disease is the second leading cause of death and the leading cause of disability worldwide. The prevalence of stroke in Indonesia increases with age. The highest stroke cases were aged 75 years and over (50.2%) and the lowest was 15-20 years (0.6%). Based on gender, male (11.0%) was more than female (10.9%). Stroke can be done by controlling lifestyle such as smoking, alcohol consumption, light physical activity, unhealthy eating patterns. The population in this study was to find stroke patients at Moewardi Hospital. Samples were outpatients at Anggrek 2 and inpatients at instalasi rehabilitasi medik totaling 30 patients. The method used is analytic observational with cross sectional design. Collecting data through direct interview techniques to the patient or the patient's guardian. The statistical test used to analyze the data in this study was the chi square test. The results of data analysis showed a relationship between diet (p=0.025 <0.05) and physical activity (p=0.010 <0.05) with the incidence of stroke at Dr Moerwardi Hospital, and there was no significant relationship between smoking (p=0.459 > 0.05) and alcohol (p = 0.309 > 0.05) with the incidence of stroke in Dr Moewardi Hospital.